Women Poets and the American Sublime - Diehl, Joanne (Indiana University Press, 1990)
"This is the best book on American women poets I have yet seen." Â -American Literature "... sophisticated and eloquently argued analysis of a female counter-sublime..." -Sandra Gilbert "... strong readings of Dickinson and Moore and... a vital polemic on behalf of feminist criticism." -Harold Bloom "This brilliant re-evaluation of major American women poets will be indispensable reading... A stunning and a magisterial achievement." -Susan Gubar "... a powerful thesis... a book that is as rich as it is dense in meaning." -The Women's Review of Books Employing current work in gender studies, psychoanalysis, and literary criticism and focusing on Emily Dickinson, Marianne Moore, Elizabeth Bishop, Sylvia Plath, and Adrienne Rich, the author delineates an alternative tradition of American women poets, what Diehl calls the American Counter-Sublime.